2023
DOI: 10.1096/fj.202301095r
|View full text |Cite
|
Sign up to set email alerts
|

POLR3G promotes EMT via PI3K/AKT signaling pathway in bladder cancer

Hualin Chen,
Lin Ma,
Wenjie Yang
et al.

Abstract: RNA Polymerase III Subunit G (POLR3G) promotes tumorigenesis, metastasis, cancer stemness, and chemoresistance of breast cancer and lung cancer; however, its biological function in bladder cancer (BLCA) remains unclear. Through bioinformatic analyses, we found that POLR3G expression was significantly elevated in BLCA tumor tissues and was associated with decreased survival. Multivariate Cox analysis indicated that POLR3G could serve as an independent prognostic risk factor. Our functional investigations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…In glioblastoma, NQO1 could facilitate EMT through the PI3K/Akt/mTOR pathway ( 39 ). Chen also reported POLR3G promotes EMT of BLCA through regulation of the PI3K/AKT pathway ( 40 ). KEGG analysis indicated an enrichment of DEGs in the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…In glioblastoma, NQO1 could facilitate EMT through the PI3K/Akt/mTOR pathway ( 39 ). Chen also reported POLR3G promotes EMT of BLCA through regulation of the PI3K/AKT pathway ( 40 ). KEGG analysis indicated an enrichment of DEGs in the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have found that the development of lung cancer and bladder cancer was associated with activation of the PI3K/Akt/mTOR and MAPK signaling pathway [30][31][32][33]. Chen et al discovered that RNA Polymerase III Subunit G (POLR3G) plays a contributory role in the development of lung cancer and bladder cancer [34]. Lung cancer and bladder cancer may share similar biological mechanisms, which could explain the causal relationship between these two cancers.…”
Section: Discussionmentioning
confidence: 99%